1996
DOI: 10.1159/000129484
|View full text |Cite
|
Sign up to set email alerts
|

Cisapride Prevents Enteric Bacterial Overgrowth and Translocation by Improvement of Intestinal Motility in Rats with Acute Liver Failure

Abstract: Enteric bacterial overgrowth resulting from compromised gastrointestinal motility has been suggested to be important for the development of enteric bacterial translocation. In the present study, the effect of cisapride, a 5-hydroxytryptamine-4-receptor agonist and stimulant of intestinal motility, was evaluated concerning intestinal motility, as measured by intestinal transit time, enteric bacterial overgrowth, and bacterial translocation from the gut in rats with acute liver failure induced by 90% hepatectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…In fact, cisapride has been reported to prevent IBO and BT by improving intestinal motility in rats with acute liver failure. 39 Moreover, in the pilot intervention study, prolonged OCT significantly decreased in cirrhotic patients after cisapride therapy. This beneficial effect was associated with the abolition of IBO caused by gram-negative organisms in 4 out of the 5 patients treated with cisapride, whereas it persisted positive in the 4 patients who did not receive cisapride administration.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, cisapride has been reported to prevent IBO and BT by improving intestinal motility in rats with acute liver failure. 39 Moreover, in the pilot intervention study, prolonged OCT significantly decreased in cirrhotic patients after cisapride therapy. This beneficial effect was associated with the abolition of IBO caused by gram-negative organisms in 4 out of the 5 patients treated with cisapride, whereas it persisted positive in the 4 patients who did not receive cisapride administration.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, selective intestinal decontamination with suppression of aerobic intestinal bacteria prevents BT in cirrhotic rats, and is the current prophylaxis for SBP in humans (17)(18)(19)(20). On the other hand, several studies have shown that impaired intestinal motility is one of the fac-tors contributing to enteric bacterial overgrowth, and also that intestinal transit is delayed in the setting of cirrhosis mainly related to the severity of disease (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Enteric bacterial overgrowth resulting from impaired GI motility has been suggested to be important for the development of enteric bacterial translocation [8]. It has been demonstrated that interdigestive small bowel motility has a regulatory function on the microflora of the upper small bowel [9].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that interdigestive small bowel motility has a regulatory function on the microflora of the upper small bowel [9]. In ICU patients, reduced GI perfusion and motility result in the sequestration of fluids and translocation of bacteria and endotoxins, and the immunological function of the gut is depressed [8]. A delay in intestinal transit appears as an early event in acute pancreatitis, preceding intestinal bacterial overgrowth and translocation.…”
Section: Resultsmentioning
confidence: 99%